EFFECTIVE METHODS OF TEACHING FOREIGN LANGUAGES TO SLOW-LEARNING UZBEK-SPEAKING LEARNERS AND THE ROLE OF RELIGION, GENDER, AND CULTURE - Ra’no Urishevna Madzidova,; Eldorbek Davlatjon’s son Khusanov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Are you, as a foreign language teacher, experiencing challenges in teaching foreign languages to school students? Does working with slow learners in your classroom particularly concern you? Do issues such as low learning achievement, lack of motivation, and the influence of cultural and social factors affect your teaching process?  If  these  questions  sound  familiar,  then  this  academic  article  is  written especially for you. Building  on  these  practical  concerns,  the  present  study  examines  effective methods  of  teaching  foreign  languages  to  low-achieving  Turkic-speaking  learners through  an  interdisciplinary  framework  combining  philology  and  pedagogics.  The article  analyzes  common  linguistic  difficulties  faced  by  Turkic-speaking  students, including  phonological,  lexical,  and  grammatical  interference,  which  often  impede successful foreign language acquisition, particularly among slow learners in school environments. From a pedagogical perspective, the study highlights the importance of differentiated  instruction,  scaffolded  learning  activities,  and  learner-centered approaches  aimed  at  increasing  motivation  and  academic  engagement.  Special attention  is  given  to  the  role  of  religion,  gender,  and  culture  as  key  socio-cultural factors influencing learners’ attitudes toward foreign language education. Respect for religious  values,  the  application  of  gender-sensitive  teaching  strategies,  and  the integration of culturally relevant materials are discussed as effective means of reducing affective barriers such as anxiety and low self-confidence.